Kaji Eksperimental Rugi-Rugi Aliran Campuran Partikel Padat-Udara Dalam Saluran Horizontal Pada Sistem Pneumatic Conveying - D.Erianto Simanjuntak; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pneumatic Conveyor is a System used to move solid particle from one site to another with air as a medium of transportation.Phenomenon that occurs in Pneumatic Conveying flow systems such as: Pressure losses, channel erosion, formation of deposits on the channel and so on. Channel erosion is seen getting bigger at the bottom of the channel. Besides that solid particles tend to be more concentrated in the bottom of the channel.Testing by varying the flow rate of mass and type of dust by regulating the opening of the channel entrance, the velocity of air flow, resulting in that increasing this variation can increase the pressure drop Channel erosion becomes large when the concentration of dust increases in flow. At the time of testing if there is a buildup in the bottom of the dust channel the system exits longer (transport is not smooth). Then the dust attached to the blower blade will be a new problem for the system. So thus increasing the concentration of dust in the flow can affect the performance of the system.Keywords: Pneumatic Conveying, Dust (Particles), Pressure drop.